Chemoselective dithioacetalization of aldehydes using silica sulfuric acid as a reusable catalyst - Pore, D. M.; Desai, Uday V.; Mane, R. B.; Wadgaonkar, P. P. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2006)
Silica sulfuric acid has been found to be an efficient and reusable catalyst for chemoselective dithioacetalization of aldehydes over ketones, in excellent yields.
Keywords: Chemoselective; dithioacetalization; silica sulfuric acid

Composites of plasma treated poly(etherimide) films with gold nanoparticles and lysine through layer by layer assembly: a ``friendly-rough'' surface for cell adhesion and proliferation for tissue engineering applications - D'Britto, Virginia; Tiwari, S.; Purohit, V.; Wadgaonkar, P. P.; Bhoraskar, S. V.; Bhonde, Ramesh R.; Bhagavatula L. V. Prasad (Journal of Materials Chemistry, 2009)
A composite film fabricated by plasma treated poly(etherimide) with subsequent deposition of gold nanoparticles and lysine using layer by layer assembly has been demonstrated to be good for cell attachment and proliferation making it an attractive strategy for tissue engineering applications. As compared to the other methods the decrease in contact angle obtained here does not depend much on the plasma treatment thus affecting the polymer structure minimally. A combination of surface roughness provided by the gold nanoparticles and the presence of amine groups of lysine is hypothesized to be the reason for the features observed.

Catalyst-free oxidation of sulfides to sulfoxides and diethylamine catalyzed oxidation of sulfides to sulfones using oxone as an oxidant - Kupwade, R. V.; Khot, S. S.; Lad, U. P.; Desai, U. V.; Wadgaonkar, P. P. (Research on Chemical Intermediates, 2017)
We describe here our journey from the failure of our attempts in controlled oxidation of sulfides to sulfoxides using an Oxone(A (R))-KBr combination to our success in the development of a catalyst-free protocol for the oxidation of sulfides to sulfoxides using Oxone as an oxidant. We also describe the failure of our attempts at the oxidation of sulfides to sulfones using an excess of Oxone-KBr as well as Oxone, and our success towards the development of a rapid, scalable and chromatography-free protocol for the oxidation of sulfides to sulfones using diethylamine-Oxone as an unprecedented catalyst-oxidant combination. [GRAPHICS] .
Keywords: diethylamine; organocatalysis; Oxidation; Oxone; Sulfones; Sulfoxides

Crystallisation-enhanced bulk hole mobility in phenothiazine-based organic semiconductors - Shinde, D. B.; Salunke, Jagadish K.; Candeias, Nuno R.; Tinti, Francesca; Gazzano, Massimo; Wadgaonkar, P. P.; Priimagi, Arri; Camaioni, Nadia; Vivo, Paola (Scientific Reports, 2017)
A series of three novel donor-acceptor systems based on C(3)-malononitrile-substituted phenothiazines was synthesised in good overall yields and their thermal, spectroscopic, and electrochemical properties were characterised. The compounds were prepared through a sequence of Ullmann-coupling, Vilsmeier-Haack formylation and Knoevenagel-condensation, followed by Suzuki-coupling reactions for introduction of aryl substitutents at C(7) position of the phenothiazine. The introduction of a donor unit at the C(7) position exhibited a weak impact on the optical and electrochemical characteristics of the compounds and led to amorphous films with bulk hole mobilities in the typical range reported for phenothiazines, despite the higher charge delocalisation as attested by computational studies. In contrast, highly ordered films were formed when using the C(7)-unsubstituted 3-malononitrile phenothiazine, exhibiting an outstanding mobility of 1 x 10(-3) cm(2) V-1 s(-1), the highest reported for this class of compounds. Computational conformational analysis of the new phenothizanes suggested that free rotation of the substitutents at the C(7) position suppresses the ordering of the system, thereby hampering suitable packing of the new materials needed for high charge carrier mobility.

Catalyst-free oxidation of sulfides to sulfoxides and diethylamine catalyzed oxidation of sulfides to sulfones using Oxone as an oxidant (vol 43, pg 6875, 2017) - Kupwade, R. V.; Khot, S. S.; Lad, U. P.; Desai, U. V.; Wadgaonkar, P. P. (Research on Chemical Intermediates, 2018)